2017
DOI: 10.1210/jc.2017-00161
|View full text |Cite
|
Sign up to set email alerts
|

Somatic USP8 Gene Mutations Are a Common Cause of Pediatric Cushing Disease

Abstract: Context:Somatic mutations in the ubiquitin-specific protease 8 (USP8) gene have been recently identified as the most common genetic alteration in patients with Cushing disease (CD). However, the frequency of these mutations in the pediatric population has not been extensively assessed.Objective:We investigated the status of the USP8 gene at the somatic level in a cohort of pediatric patients with corticotroph adenomas.Design and Methods:The USP8 gene was fully sequenced in both germline and tumor DNA samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
96
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 30 publications
11
96
3
1
Order By: Relevance
“…Previous studies have postulated a role for USP8 mutational status as predictor of long‐term remission. Patients with USP8 mutant tumours presented with higher 24‐hours‐UFC levels and impaired ACTH reduction after surgery, and paediatric CD patients with USP8 mutant tumours showed higher recurrence rate . Another study suggested a shorter mean recurrence period in USP8 mutants (months 29 vs 48) in a subset of adult CD patients that recurred .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have postulated a role for USP8 mutational status as predictor of long‐term remission. Patients with USP8 mutant tumours presented with higher 24‐hours‐UFC levels and impaired ACTH reduction after surgery, and paediatric CD patients with USP8 mutant tumours showed higher recurrence rate . Another study suggested a shorter mean recurrence period in USP8 mutants (months 29 vs 48) in a subset of adult CD patients that recurred .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we have shown higher 24‐hour urinary‐free cortisol (UFC) levels and impaired ACTH reduction after surgery in patients with USP8 mutant tumours, suggesting that they may present with higher rate of recurrence . Indeed, a study on paediatric CD patients reported higher recurrence rate in those with USP8 mutant tumours . However, the impact of the USP8 mutational status on long‐term recurrence in adult CD patients remains inconclusive.…”
Section: Introductionmentioning
confidence: 98%
“…This results in an increased activation of EGFR signaling and subsequent induction of proopiomelanocortin (POMC) transcription and ACTH secretion . Mutations in the USP8 gene have been identified in around one‐third of both adult and pediatric population affected by CD and have been connected to a higher rate of tumor recurrence after surgical resection of the pituitary adenomas .…”
mentioning
confidence: 99%
“…This results in an increased activation of EGFR signaling and subsequent induction of proopiomelanocortin (POMC) transcription and ACTH secretion [8]. Mutations in Abbreviations ACTH, adrenocorticotropic hormone; CD, Cushing's disease; DUB, deubiquitinating enzyme; EGFR, epidermal growth factor receptor; FP, fluorescence polarization; ITC, isothermal titration calorimetry; PPI, protein-protein interaction; USP8, ubiquitin-specific protease 8. the USP8 gene have been identified in around onethird of both adult and pediatric population affected by CD and have been connected to a higher rate of tumor recurrence after surgical resection of the pituitary adenomas [9,10].…”
mentioning
confidence: 99%
“…Patients with USP8 mutations from our cohort have been reported elsewhere (Pérez-Rivas et al 2015, Faucz et al 2017). …”
Section: Methodsmentioning
confidence: 99%